Numbing of Positive, Negative, and General Emotions: Associations With Trauma Exposure, Posttraumatic Stress, and Depressive Symptoms Among Justice‐Involved Youth. Issue 2 (April 2016) - Kerig, Patricia K.; Bennett, Diana C.; Chaplo, Shannon D.; Modrowski, Crosby A.; McGee, Andrew B.
Abstract : Increasing attention has been drawn to the symptom of emotional numbing in the phenomenology of posttraumatic stress disorder (PTSD), particularly regarding its implications for maladaptive outcomes in adolescence such as delinquent behavior. One change in the definition of emotional numbing according to the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM‐5 ; American Psychiatric Association, 2013) was the limitation to the numbing of positive emotions. Previous research with youth, however, has implicated general numbing or numbing of negative emotions in PTSD, whereas numbing of positive emotions may overlap with other disorders, particularly depression. Consequently, the goal of this study was to investigate whether numbing of positive emotions was associated with PTSD symptoms above and beyond numbing of negative emotions, general emotional numbing, or depressive symptoms among at‐risk adolescents. In a sample of 221 detained youth (mean age = 15.98 years, SD = 1.25; 50.7% ethnic minority), results of hierarchical multiple regressions indicated that only general emotional numbing and numbing of anger accounted for significant variance in PTSD symptoms (total R 2 = .37). In contrast, numbing of sadness and positive emotions were statistical correlates of depressive symptoms (total R 2 = .24). Further tests using Hayes' Process macro showed that general numbing, 95% CI [.02, .45], and numbing of anger, 95% CI [.01, .42], demonstrated indirect effects on the association between trauma exposure and PTSD symptoms.